Clinical and haematological features of newborns of mothers with hypertensive disorders in pregnancy in Lagos, Nigeria (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Abstract: Background: Newborns of mothers with hypertensive disorders in pregnancy have an increased risk of preterm delivery, low birth weight, perinatal asphyxia and haematological derangements such as polycythaemia, thrombocytopenia and neutropenia. These morbidities are associated with uteroplacental insufficiency. The haematological derangements however have not been studied in detail in African neonates.Objective: To determine the clinical and haematological features of newborns of hypertensive mothers Methods: Cross-sectional study involving 250 newborns; 125 newborns each of hypertensive mothers (cases), and normotensive mothers (controls). The babies were examined following delivery, their clinical data were recorded, and umbilical cord blood samples were analysed for haematological indices.Results: Preterm deliveries were significantly higher amongst infants of hypertensive mothers (31.2%) compared with controls (12.0%); p = 0.000. Similarly, the birth weight, length and head circumference of the cases were significantly lower than the controls; p = 0.008, 0.003 and 0.004 respectively. Low fifth minute APGAR scores occurred more frequently in cases (8.0%) than controls (0.8%), p=0.010; whilst the mean haematocrit was also significantly higher in cases than the controls, p = 0.013. The median absolute neutrophil count and platelet count were significantly lower in cases than controls; p=0.023 and 0.047 respectively. Thrombocytopenia was identified in 40.0% of the cases compared to 27.2% of the controls, p = 0.041Conclusion: The present study has shown that newborns of hypertensive mothers have an increased risk of neonatal morbidities such as preterm birth, LBW and thrombocytopenia compared to the newborns of mothers with normal blood pressure in pregnancy, hence close attention needs to be paid to them with emphasis on their haematological system.Keywords: newborn, pregnancy, hypertension, hypertensive disorders, haematological, clinical